Odpowiedź :
a)
[tex]( \frac{13}{12} - \frac{7}{15} ) \div \frac{37}{30} - \frac{3}{4} = (\frac{65}{60} - \frac{28}{60} ) \times \frac{30}{37} - \frac{3}{4} = \frac{37}{60} \times \frac{30}{37} - \frac{3}{4} = \frac{1}{2} - \frac{3}{4} = \frac{2}{4} - \frac{3}{4} = - \frac{1}{4} [/tex]
b)
[tex] - 4 \frac{3}{4} - 4 \times ( \frac{3}{2} - 1.9) = - \frac{19}{4} - 4 \times ( \frac{3}{2} - \frac{19}{10}) = - \frac{19}{4} - 4 \times ( \frac{15}{10} - \frac{19}{10} ) = - \frac{19}{4} - 4 \times ( - \frac{4}{10} ) = - \frac{19}{4} + \frac{8}{5} = - \frac{95}{20} + \frac{32}{20} = - \frac{63}{20} = - 3 \frac{3}{20} = - 3.15[/tex]
Odpowiedź:
a) ( 13/12 -7/15) : 37/30 -3/4= (65/60 - 28/60) : 74/60 - 3/4=
= 37/60 : 74/60-3/4= 37/60* 60/74 -3/4 ( skracamy 60 i 60 przez 60,
oraz 74 i 37 przez 37) -3/4= 1/2- 3/4= 2/4- 3/4= - 1/4
b) - 4 i 3/4 - 4 *( 3/2 - 1,9)= - 4 i 3/4 - 4( 3/2- 1 i 9/10)= -4 i 3/4-4*( 15/10- 19/10)=
= - 4 i 3/4 - 4*(-4/10)= - 4 i 3/4 + 16/10= - 4 i 3/4+ 1 i 6/10=
= - 4 i 15/20+ 1 i 12/20= - 3 i 3/20
Szczegółowe wyjaśnienie: